Econet of Ukraine: ideology of creation and formation ways (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
It was analyzed the international experience of formation of the national econets. Ideology of econet’s creation in Ukraine has been considered, and there have been described the main stages of its formation. The prospective scheme of the econet of the Chernigov Region’s northern part is presented.
Keywords: econet, structural components, key areas, connected areas, buffer areas, restored areas.